The Effects of Cueing and Framing on Youth Attitudes towards Gun Control and Gun Rights - Stephen Wu (Social Sciences, 2018)
I analyze attitudes towards gun control from a recent survey of American high school students. For students who most closely identify as Republicans, cueing them to think about prior school shootings increases their agreement that armed staff in schools will improve safety and arming citizens will reduce risk of mass shootings. For those identifying as Democrats and Independents, providing them with selective information that certain states have loose gun control laws and low rates of gun violence makes them more supportive of gun rights. For Republicans, providing selective information that certain states have loose gun control laws and high rates of gun violence makes them less supportive of gun rights. These results suggest that emotional cues may exacerbate a priori biases, while informational cues may be more likely to change people’s minds about firearm policies.